The Integration of Knowledge and Theory of Planned Behavior towards Purchase Intention among Consumers - Dzulkipli, Mohd Redhuan; Maon, Siti Noorsuriani; Anuar, Annurizal (Information Management and Business Review, 2023)
Considering the rising cost of medicine in Malaysia, it is crucial to investigate the behavioral factors that influence the intent of consumers when selecting medicines. Thus, the main objective of this paper is to examine the influence of the Theory of Planned Behavior (TPB) and respondents’ knowledge on their intentions to purchase either generic or brand-name medicines. A cross-sectional survey research design was used in this study, involving consumers in various community areas in Selangor. Using a convenience sampling approach, a total of 444 respondents participated in this study. More than half of the respondents were female (63%) and Malay (73%). In regression analysis, the results showed that knowledge (p <0.001) and perceived behavioral control (p <0.001) were statistically significant for purchase intention toward generic and brand medicine. Though statistically significant, only 19% and 29% (knowledge and perceived behavioral control) of the respondents showed intention to purchase the generic medicine while a higher percentage of the respondents showed agreement to their purchase intention with 27% and 45% of the same variables for the purchase intention to the brand medicine. Knowledge and perceived behavioral control were found to be predictors of respondents’ intentions to purchase either generic or brand-name medicines. Apart from that, the perceived capacity to purchase is one of the factors that determine consumers’ purchase intent. The people’s awareness of the similarity between brand-name medicines needs to be increased, as well an individual’s ability to pay for the medicine should be explored in future research